Differential Functional Responses of Neutrophil Subsets in Severe COVID-19 Patients - McLeish, Kenneth R.; Shrestha, Rejeena; Vashishta, Aruna; Rane, Madhavi J.; Barati, Michelle T.; Brier, Michael E.; Lau, Mario Gutierrez; Hu, Xiaoling; Chen, Oscar; Wessel, Caitlin R.; Spalding, Travis; Bush, Sarah E.; et al. (Frontiers in Immunology, 2022)
Neutrophils play a significant role in determining disease severity following SARS-CoV-2 infection. Gene and protein expression defines several neutrophil clusters in COVID-19, including the emergence of low density neutrophils (LDN) that are associated with severe disease. The functional capabilities of these neutrophil clusters and correlation with gene and protein expression are unknown. To define host defense and immunosuppressive functions of normal density neutrophils (NDN) and LDN from COVID-19 patients, we recruited 64 patients with severe COVID-19 and 26 healthy donors (HD). Phagocytosis, respiratory burst activity, degranulation, NET formation, and T-cell suppression in those neutrophil subsets were measured. NDN from severe/critical COVID-19 patients showed evidence of priming with enhanced phagocytosis, respiratory burst activity, and degranulation of secretory vesicles and gelatinase and specific granules, while NET formation was similar to HD NDN. COVID LDN response was impaired except for enhanced NET formation. The subset of COVID LDN with intermediate CD16 expression (CD16Int LDN) promoted T cell proliferation and IFN production, while COVID NDN and the CD16Hi subset of COVID LDN suppressed T-cell activation, compared to HD NDN. We conclude that NDN and LDN from COVID-19 patients possess complementary functional capabilities that may act cooperatively to determine disease severity. We predict that global neutrophil responses that induce COVID-19 ARDS will vary depending on the proportion of neutrophil subsets.